Tree ring research may understand climate change / Nur Idzhainee Hashim and Rob Marrs - Hashim, Nur Idzhainee; Rob, Marrs (UiTM Cawangan Negeri Sembilan, 2023)
Dendrochronology is the scientific discipline of determining the relationship between tree growth and climate, and is determined using the annual growth rings. This provides a potential method for monitoring climate change. Climate usually acts as a major factor influencing the tree growth. Here, the effects of climate of a conifer species was assessed in relation to measured climatic variables. Tree cores of Scots Pine (Pinus sylvestris) were sampled from a forestry plantation at Hordron Edge, Derbyshir. Standard dendrochronological techniques were used to collect, prepare and measure tree – ring width increments. Forest ecosystems have been recognized as an essential component of the biosphere (Hooper et. al., 2005). One of the most widely–distributed conifers tree in the world is Scots Pine (P. sylvestris) (Royal Forestry Society, 2014). It is found naturally in Great Britain mainly in the Scottish Highlands but is planted extensively throughout the country. It is evergreen, reaching heights of 25 m to 45 m when mature, and is classified as softwood which makes it easy to extract tree cores.